An alternative measure of positive correlation. Issue 4 (19th May 2019) - Nadarajah, Saralees; Chu, Jeffrey; Chan, Stephen
ABSTRACT: A correlation coefficient taking positive values is introduced. It is more easily understood than other correlation measures especially in social science contexts. Estimation issues are addressed. A data application is given.